Assessment of Eco-Physiological Performance of Quercus ilex L. Leaves in Urban Area by an Integrated Approach - Arena, Carmen; De Maio, Anna; De Nicola, Flavia; Santorufo, Lucia; Vitale, Luca; Maisto, Giulia (WATER AIR AND SOIL POLLUTION, 2014)
Plant physiological performance may be endangered in contaminated urban areas. Metal and polycyclic aromatic hydrocarbon (PAH) content in Quercus ilex leaves mainly reflects air pollution, being for these pollutants traceable the translocation from soil. In this work, in a field study, the responses at structural and functional level of Q. ilex leaves to metal and PAH pollution were assessed by an integrated approach. At this purpose, morphological (functional traits), biochemical (pigment content, antioxidant capacity, and PARP activity), and physiological (partitioning of absorbed light in the photosynthetic process) analyses were performed in leaves collected at urban parks and roadsides. Compared to the leaves of the urban parks, those sampled at the roadsides showed higher metal and PAH accumulation. The most contaminated leaves showed smaller leaf sizes and lower relative water and pigment content, as well as a lower photochemistry. In this circumstance, the excess of absorbed light at PSII was mainly dissipated via non-regulated than heat processes. On the basis of the biochemical analyses, the occurrence of DNA damages in contaminated Q. ilex leaves may be hypothesized.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: PAH and metal contamination; PARP activity; Photochemistry; Q. ilex

An assessment of the influence of the urban environment on collembolan communities in soils using taxonomy- and trait-based approaches - Santorufo, Lucia; Cortet, Jérôme; Arena, Carmen; Goudon, Romain; Rakoto, Alain; Morel, Jean-Louis; Maisto, Giulia (Applied Soil Ecology, 2014)
In this study we investigated collembolan communities using both taxonomy- and trait-based approaches in order to determine: (1) which soil or leaf litter characteristics are the main agents of species distribution and functional trait distribution in collembolan communities, and (2) which functional traits are more prevalent in species tolerant to urban environments. To investigate this, soil and leaf litter were sampled in the urban area of Naples, Italy and the collembolan community was analyzed using taxonomic and functional approaches. The results indicated that collembolan density was negatively affected by site pollution, and that species richness, diversity and evenness were positively affected by the organic matter content of the soil. Folsomia lawrencei was the most abundant species in sites with high metal contamination and low soil organic matter content, whereas Mesaphorura sp. and Parisotoma notabilis were the most ubiquitous taxa overall. The main agents affecting the frequency of functional traits were metal contamination of soil and litter, soil organic matter content, leaf specific mass and thickness of the litter. The species most tolerant to urban environmental conditions were found to have small body size, jumping motion strategy, sexual reproduction and presence of pigmentation.
Keywords: Collembola; Metal contamination; Organism traits; Urbanization

Heavy metal accumulation in leaves affects physiological performance and litter quality of Quercus ilex L. - Maisto, Giulia; Santorufo, Lucia; Arena, Carmen (JOURNAL OF PLANT NUTRITION AND SOIL SCIENCE, 2013)
This study aimed to investigate the relationships between leaf functional modifications and heavy metal concentrations of Quercus ilex L., a good bioindicator of air quality. In addition, as metal concentration in litter plays an important role in decomposition and, in turn, in biogeochemical cycles, samples of undecomposed and whole-leaf litter were analyzed for heavy metals. Leaves and leaf litter of Q. ilex were collected at six sites (roadsides, motorway sites, and urban parks) in Naples (Southern Italy) and characterized for Cd, Cr, Cu, Ni, and Pb concentrations. The investigated functional leaf traits were: leaf area (LA), specific leaf area (SLA), leaf dry-matter content (LDMC), water content (WC), leaf relative water content (RWC), maximal PSII photochemical efficiency (F-v/F-m, variable fluorescence / maximal fluorescence), and total chlorophyll concentration. The motorways were the most contaminated sites, and Pb was the main responsible source of contamination. The metal contamination caused slight variation of F-v/F-m, suggesting that metals did not significantly alter functionality of the photosynthetic apparatus. On the other hand, it can be supposed that higher leaf deposit can cause an increase of pigment biosynthesis in response to the shading increase caused by dust deposition.
Keywords: Bioindicator; heavy metal contamination; leaf traits; maximum PSII photochemical efficiency; Urban environment